Predictive testing for neurodegenerative diseases in the age of next‐generation sequencing. Issue 2 (8th October 2020) - Goldman, Jill; Xie, Shanghong; Green, Dina; Naini, Ali; Mansukhani, Mahesh M.; Marder, Karen
Abstract: The availability and cost of next‐generation sequencing (NSG) now allow testing large numbers of genes simultaneously. However, the gold standard for predictive testing has been to test only for a known family mutation or confirmed family disease. The goal of this study was to investigate the psychological impact of predictive testing for autosomal dominant neurodegenerative diseases without a known family mutation using next‐generation sequencing panels compared to single‐gene testing of a known family mutation. Fourteen individuals from families with a known mutation and 10 individuals with unknown family mutations participated. Participants completed questionnaires on demographics, genetic knowledge, and psychological measures of anxiety, depression, perceived personal control, rumination, and intolerance to uncertainty at baseline and 1 and 6 months after receiving results. Decision regret was measured 1 and 6 months after receiving results. Participants completed a modified Huntington disease genetic testing protocol with genetic counseling and neurological and psychological evaluation. Genetic testing of either the known family mutation or an NGS panel of neurodegenerative disease genes was performed. Semi‐structured interviews were performed at 6 months post‐results about their experience. Two‐sample t tests were performed on data collected at each time point to identify significant between‐group differences in demographic variables, baseline psychological scores, and baseline genetic knowledge scores. Within‐group change over time was assessed by a mixed‐effects model. Results of this study indicate that NGS panels for predictive testing for neurodegenerative disease are safe and beneficial to participants when performed within a modified HD protocol. Though significant differences in psychological outcomes were found, these differences may have been driven by genetic results and baseline psychological differences between individuals within the groups. Participants did not regret their decision to test and were largely pleased with the testing protocol.